The Effectiveness of the Situational Leadership Style of PT. Fajar Makassar Television (Fajar TV) - Darwis, Muh; Putra, Virdi; Niswaty, Risma; Takdir, Muhammad; Mannayong, Jumalia (Universitas Negeri Makassar, 2021)
In essence, employees are trusted colleagues and are expected to be able to provide new ideas and ideas that are needed by the company. This study aims to determine the effectiveness of the leadership of the PT. Fajar Makassar Television (FAJAR TV). To achieve this goal, the researcher determined 5 (five) informants with the type of research and the approach used was descriptive qualitative. Collecting data through interview techniques, observation, and documentation. The results showed that, the leadership of PT. Fajar Makassar Televisi (FAJAR TV) has implemented its situational leadership well, with the involvement of the leader in determining and assigning tasks to employees that have been running optimally, implementing relationship behavior with employees well, and the attitude of the leadership in responding to the readiness of followers effectively. So the application of the leadership of the PT. Fajar Makassar Televisi (FAJAR TV) has been running effectively.